Effectiveness of water pressure method in colorectal endoscopic submucosal dissection by novice endoscopists - Masunaga, Teppei; Kato, Motohiko; Sasaki, Motoki; Iwata, Kentaro; Miyazaki, Kurato; Kubosawa, Yoko; Mizutani, Mari; Takatori, Yusaku; Matsuura, Noriko; Nakayama, Atsushi; Takabayashi, Kaoru; Yahagi, Naohisa (Endoscopy International Open, 2023)
Background and study aims Colorectal endoscopic submucosal dissection (ESD) remains challenging for novice endoscopists. Not only the underwater conditions but also active use of water pressure with the water pressure method (WPM) can help widen the submucosal layer. This study aimed to clarify the usefulness of WPM in colorectal ESD, especially for novice endoscopists.Methods This study was ex vivo and enrolled three novices. Each endoscopist performed conventional ESD (C-ESD) and ESD with WPM (WPM-ESD) 10 times on an excised bovine rectum. The treatment outcomes were compared between the two groups.Results Median procedure time was significantly shorter in the WPM-ESD group than in the C-ESD group (54 minutes, interquartile range [IQR] 42–67 vs. 45 minutes, IQR 34–55, P = 0.035). Although no significant difference in the activation time of electrical surgical unit (ESU) during the procedure was noted, the interval time during the procedure at which the ESU was not activated was significantly shorter in the WPM-ESD group (52 minutes, IQR 40–65 vs. 42 minutes, IQR 32–52, P = 0.030) than in the C-ESD group. Moreover, the time required for the endoscope to enter the submucosa was significantly shorter in the WPM-ESD group than in the C-ESD group (8.0 minutes, IQR 6.0–10 vs. 5.0 minutes, IQR 3.0–6.0, P < 0.001).Conclusions The present study reveals that the WPM method significantly shortens the procedure times for novices in colorectal ESD, especially the interval time, which refers to the time spent creating the field of view, and the time required for the endoscope to enter the submucosa.
Keywords: Endoscopy Lower GI Tract; Colorectal cancer; Endoscopic resection (polypectomy, ESD, EMRc, ...)